Perancangan Simbol Angka Numerik Aksara Lontara - Abd Azis Ahmad; Ali Ahmad Muhdy; Baso Indra Wijaya Azis (Seminar Nasional LP2M UNM, 2019)
This study aims to examine and design: Prototype of numerical symbols of Lontara alphabet which is valid and practical and in harmony with the character of Lontara script. Methodologically this research was carried out through research and development procedures (Research and Development), with field trials. In the operationalization of this study, the procedure formulated by Borg and Gall was used. Data was collected by searching literature, documenting, distributing questionnaires to Fine Arts Education Study Program students and lecturers of Fine Arts Education Study Programs, and in-depth interviews with observers of Lontara script development. Data analysis using interactive analysis models, there are three steps that interact with one another in the form of cycles. The three steps are; data reduction, data presentation to be used as material for revision and drawing conclusions. The results showed that, all Lontara script designs which were the product of this study, were based on the basic pattern of the two Lontara scripts namely the basic pattern of the letter "SA" and the merging of two "SA" namely the letter "HA". In the initial design process, Lontara script as a research instrument was distributed to a number of respondents. There are four redesigned symbol numbers namely; the number 0 (zero) is reduced, the number 1 (one) is omitted from the angular shape of the 'head', the number 5 (five) is reversed while the number 7 (seven) is redesigned by shortening the lines on the angular shape of the 'head'.